IgG opsonization of merozoites: multiple immune mechanisms for malaria vaccine development. Issue 10 (September 2017) - Hill, Danika L.; Schofield, Louis; Wilson, Danny W.
Graphical abstract: Highlights: Key immune mechanisms directed by opsonising antibodies against Plasmodium spp. host cell invading merozoites are described. Evidence that specific immune mechanisms (e.g. phagocytosis) contribute to protection from disease is discussed. Key assays are important for gaining insights into different immune mechanisms and for vaccine development. Interconnected immune mechanisms directed by opsonising antibodies and the requirement for further insights are discussed. Abstract: Global eradication of the human-infecting malaria parasite Plasmodium falciparum, the major cause of malaria mortality, is unlikely to be achieved without an effective vaccine. However, our limited understanding of how protective immune responses target malaria parasites in humans, and how to best elicit these immune responses through vaccination, has hampered vaccine development. The red blood cell invading stage of the parasite lifecycle (merozoite) displays antigens that are attractive vaccine candidates as they are accessible to antibodies and raise high antibody titres in naturally immune individuals. The number of merozoite antigens that elicit an immune response, and their structural and functional diversity, has led to a large number of lead antigens being pursued as vaccine candidates. Despite being seemingly spoilt for choice in terms of vaccine candidates, there is still a lack of consensus on exactly how merozoite antibodies reduce parasitemia and malaria disease. In this review we describe the various immune mechanisms that can result from IgG opsonization of merozoites, and highlight recent developments that support a role for these functional antibodies in naturally acquired and vaccine-induced immunity.